1987
DOI: 10.1136/bmj.294.6576.859
|View full text |Cite
|
Sign up to set email alerts
|

Clinically apparent eating disorders in young diabetic women: associations with painful neuropathy and other complications.

Abstract: Of 208 young women with insulin dependent diabetes, 15 (7%) had a clinically apparent eating disorder (anorexia nervosa or bulimia), a much higher prevalence than reported in non-diabetic women. Most, but not all, of these patients had a long history of poor glycaemic control. In contrast with previous suggestions, control did not deteriorate after the onset of the eating disorder. There was a high incidence and an early onset of diabetic complications. Eleven ofthe 15 patients had retinopathy, six with prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
2
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(93 citation statements)
references
References 25 publications
(9 reference statements)
3
86
2
2
Order By: Relevance
“…This is an important mediator of the association of DEB and EDs with poorer metabolic control (5,6) and contributes to an increased risk of a range of short-term and long-term diabetes-related medical complications. These include abnormal lipid profiles (7), diabetic ketoacidosis (6), retinopathy (8), neuropathy (9), and nephropathy (10), as well as higher than expected mortality (11).…”
mentioning
confidence: 99%
“…This is an important mediator of the association of DEB and EDs with poorer metabolic control (5,6) and contributes to an increased risk of a range of short-term and long-term diabetes-related medical complications. These include abnormal lipid profiles (7), diabetic ketoacidosis (6), retinopathy (8), neuropathy (9), and nephropathy (10), as well as higher than expected mortality (11).…”
mentioning
confidence: 99%
“…The relationship between higher weight and DEB presents a management dilemma for clinicians, since both dietary restraint and higher weight are clear risk factors for the development of ED and their negative health consequences. Although until recently it has been unclear whether there is a specific association of eating disorders with diabetes, some studies have suggested an increased incidence of eating disorders in young women with diabetes (Birk & Spencer, 1987;Engstrom et al, 1999;Hudson et al, Lloyd et al, 1987;Rodin et al, 1985;Rodin et al, 1986Rodin et al, /1987Rodin et al, 1991;Rosmark et al, 1986;Stancin et al, 1989;Steel et al, 1987;Vila, et al, 1993;Vila et al, 1995) whereas others did not find such an increase Fairburn et al, 1991;Friedman et al, 1995;Mannucci et al, 1995;Marcus et al, 1992;Meltzer et al, 2001;Powers et al, 1990;Robertson & Rosenvinge, 1990;Striegel-Moore et al, 1992;Wing et al, 1986). However, the conclusions of these studies are limited by the small sample sizes of females in the age of the highest risk for eating disturbances, the absence of control groups, their low statistical power, and/or by the lack of structured diagnostic interviews for the assessment of eating disorders.…”
Section: Inadequate Coping Attitudes In Type 1 Diabetic Patientsmentioning
confidence: 99%
“…If this behavior continues, it may also result in kidney failure, eye disease leading to blindness, vascular disease and even death. In particular, patients who misuse insulin to control body weight (Crow et al, 1998;Rodin et al, 1989), are thought to be at increased risk for microvascular complications (Rydall et al, 1997;Steel et al, 1987), but the extent of the risk has not been well characterized, as most studies have been cross-sectional. Clinical outcome in terms of physical and psychological health are not known with certainty.…”
Section: Metabolic Consequences and Vascular Complications Of Disordementioning
confidence: 99%
“…Despite a lack of rigorous epidemiological study, certain populations of medical patients are also thought to be at greater risk of eating disorder (Patton et al 1986). The most well known of these are young diabetic women, where the development of eating disorders following the onset of diabetes raises the interesting possibility that the special diet of these subjects may be contributory (Steel et al 1987(Steel et al , 1990.…”
Section: Key Issuesmentioning
confidence: 99%